Biomimetic Opaque Ventilated Façade for Low-Rise Buildings in Hot Arid Climate - Ahmed Alyahya; Simon Lannon; Wassim Jabi (Buildings)
Enhancing the thermal performance of building façades is vital for reducing energy demand in hot desert climates, where envelope heat gain increases cooling loads. This study investigates the integration of biomimicry into opaque ventilated façade (OVF) systems as a novel approach to reduce façade surface temperatures. Thirteen bio-inspired façade configurations, modeled after strategies observed in nature, were evaluated using computational fluid dynamics simulations to assess their effectiveness in increasing airflow and reducing inner skin surface temperatures. Results show that all proposed biomimetic solutions outperformed the baseline OVF in terms of thermal performance, with the wide top mound configuration achieving the greatest temperature reduction—up to 5.9 °C below the baseline OVF and 16.4 °C below an unventilated façade. The study introduces an innovative methodology that derives façade design parameters from nature and validates them through simulation. These findings highlight the potential of nature-based solutions to improve building envelope performance in extreme climates.